pH Nonlinearly Dominates Soil Bacterial Community Assembly along an Altitudinal Gradient in Oak-Dominant Forests - Lin, Litao; Li, Guixiang; Yu, Huiyi; Ma, Keming (Microorganisms (Basel), 2024)
Soil bacteria, the predominant microbiota in soil, are subject to the law of minimum and the law of tolerance, but the assembly patterns of soil bacteria in response to environmental factors remain far from clear. Here, we took advantage of an altitudinal gradient (1020–1770 asl) in oak-dominant forests and assessed whether soil bacteria linearly or nonlinearly respond to environmental properties through the changes in the community diversity and composition. We found that soil bacteria decreased with increasing altitude in terms of the species richness and phylogenetic structure, while they were unchanged with increasing altitude in terms of community composition. The species richness was nonlinearly affected by the soil pH (19.9%), C:N ratio (14.3%), SOC (11.4%), and silt + clay content (9.9%). Specifically, the species richness peaked at a pH of 5.5–6.5, and an SOC of 25–50 g kg−1, and it showed abrupt decreases and increases at a C:N ratio of 14.5 and a silt + clay content of 70%. The community composition was significantly affected by the soil pH (28.2%), then by the SOC (3.6%), available phosphorus (1.0%), and silt + clay content (0.5%), and it showed less turnovers at a pH of 6.0, SOC of 50 g kg−1, and available phosphorus > 3.0 g kg−1. These findings imply that environmental filtering processes nonlinearly shape bacterial communities.